Analisis Pedagogi Produktif Guru Matematika di SMA - Djam'an, Nurwati; Arsyad, Nurdin; Rahmayani, Rahmayani (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
This study aims to analyze the productive pedagogies of mathematics teachers at SMA Negeri 2 Makassar, focusing on four key dimensions: intellectual quality, connectedness, recognition of difference, and a supportive classroom environment. Two teachers were selected through purposive sampling, one certified and one uncertified. Data was collected through observation, interviews, and questionnaires and analyzed using data condensation, data display, and conclusion drawing, with technique triangulation employed to ensure data validity. The findings indicate that both teachers demonstrated very high capabilities in the dimension of the supportive classroom environment. In the intellectual quality dimension, both were categorized as high. In the recognition of different dimensions, the certified teacher was in the very high category, while the uncertified teacher was classified as high. However, in the connectedness dimension, the accredited teacher demonstrated moderate capability, whereas the uncertified teacher was categorized as having high capability. These results suggest that both teachers implemented productive pedagogies, although their levels of achievement varied across different dimensions.